A Meta Heuristic Optimized Localization for Efficient Deployment of Nodes in Wireless Sensor Networks - Sridevi, R.; Jagajothi, G. (International Journal of Engineering and Technology, 2018)
The main issue in the Wireless Sensor Networks (WSN) comprises computing the sensor node positions (base stations) in order to obtain energy efficiency, coverage and required connectivity with as small number of nodes as possible. Whenever incidents take place in  areas which do not have sufficient number of nodes, they are not noticed. Whereas, in places where there are more than required sensors, there is a lot of delay and congestion. Placing the sensor nodes strategically so as to obtain desired goals in throughput is one of the design optimization techniques. We explore a new heuristic called the fish swarm to determine the optimal solution for node deployment by making use of energy as well as Packet Delivery Ratio (PDR).  Improvements have been experimentally shown over strategy that is randomly placed.
Keywords: Wireless Sensor Network (WSN); Localization; Heuristic Optimization and Fish Swarm Optimization (FSO)